Feeding Habits and Reproductive Biology of Newly Discovered Endemic Glassfish, Parambassis waikhomi Geetakumari & Basudha, 2012 of Manipur - Ibungo, Ningombam; Motilan , Yurembam; Bhattacharya, Anindita; Sarkar , Prabal; Lokeshwor , Yumnam (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Parambassis waikhomi Geetakumari & Basudha, 2012, locally called Ngamhai in Manipuri dialect, is carnivorous in nature, mainly feeds on zooplankton, larvae, nymph etc. The alimentary canal of P. waikhomi is short with well demarcated stomach, and villiform teeth in both the jaws. The values of relative gut length (RGL) ranges from 0.44–0.5 for the specimens whose gut length ranges from 24.12–30.6 mm and body size range from 50–70 mm in total length of body. The maximum values of Gonado-somatic index (GSI) for males and females were observed in April i.e., 1.9439 and 10.2976 respectively. The absolute fecundity determined in the size range of 43.52–63.15 mm in total length and 1.51–4.95 g in body weight ranged from 16860 eggs for ovary weight of 0.15g to 55076 eggs for ovary weight of 0.49g. The species generally breed on pre-monsoon (March). These findings will be helpful for aquaculturist and fisheries resource management strategies as this is an endemic potential ornamental species which can be introduced in ornamental fish industries and its popularization to the rest of the world.